1993
DOI: 10.1164/ajrccm/148.4_pt_1.1002
|View full text |Cite
|
Sign up to set email alerts
|

Amiloride Inhalation Therapy in Cystic Fibrosis: Influence on Ion Content, Hydration, and Rheology of Sputum

Abstract: Amiloride inhalation as treatment for cystic fibrosis (CF) lung disease has been shown in independent studies to increase mucus clearance by ciliary and/or cough action and to retard the decline in lung function. It is hypothesized that amiloride therapy decreases the excess sodium and water absorption that is a characteristic of CF airway epithelium and that it leads to an improvement in the rheologic properties of mucus favoring airway mucus clearance. The aim of this study was to investigate whether amilori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(33 citation statements)
references
References 20 publications
5
28
0
Order By: Relevance
“…The role of epithelial Na ϩ channels in maintaining the middle ear cavities free of fluid (43,44) suggests that downregulation of Na ϩ channel activity may also underlie the known association between influenza infections and otitis media (11,45). Finally, our observation that influenza hemagglutinin inhibits Na ϩ channel activity may point the way to the development of a novel alternative to the use of Na ϩ channel blockers such as amiloride in the treatment of the Na ϩ channel overactivity seen in cystic fibrosis (46). …”
Section: ϫ2mentioning
confidence: 92%
“…The role of epithelial Na ϩ channels in maintaining the middle ear cavities free of fluid (43,44) suggests that downregulation of Na ϩ channel activity may also underlie the known association between influenza infections and otitis media (11,45). Finally, our observation that influenza hemagglutinin inhibits Na ϩ channel activity may point the way to the development of a novel alternative to the use of Na ϩ channel blockers such as amiloride in the treatment of the Na ϩ channel overactivity seen in cystic fibrosis (46). …”
Section: ϫ2mentioning
confidence: 92%
“…However, we estimated the percent dry weight (percentage of solids) of normal mucus at ϳ1.5-2.5% and of thick CF-like mucus at ϳ6 -15%, based on data reported from cell culture (26), a mouse model (4), and human studies (27)(28)(29)(30)(31)(32)(33). Mucus of 1.5% solids may be less than the normal optimal concentration because the network of mucin fibers and transport were heterogeneous (Fig.…”
Section: Figurementioning
confidence: 99%
“…1C), may reflect the concentration of mucins that occurs in larger airways due to increased mucin secretion and ASL volume absorption (36). The higher concentration of mucus we operationally chose to mimic CF, 6.5%, likely represents the minimum concentration found in CF airways before infection (29,30,32,33). Mucus transport assays demonstrated that 6.5% mucus was too thick to be transported by cilia, mimicking a key feature of CF mucus (2).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Although measurements of mucus concentration, i.e., the percentage of solids content, from CF subjects before infection have not been reported, estimates from cell cultures (11) and sputum (12)(13)(14)(15)(16)(17)(18) suggest that CF mucus is at least three or four times more concentrated than normal. Therefore, mucus was obtained from well differentiated human airway cultures and was isotonically concentrated (1) to produce mucus of normal (2.5% solids wt/wt) and CF-like (8%) concentrations (Fig.…”
mentioning
confidence: 99%